Community-Based Tourism for Sustainable Development in Kampung Lali Gadget: Pariwisata Berbasis Masyarakat untuk Pembangunan Berkelanjutan di Kampung Lali Gadget - Putri Amalia Zahroh; Vidya Imanuari Pertiwi (Academia Open, 2025)
General background: Tourism is a strategic driver of Indonesia’s post-pandemic economic recovery, yet it faces pressure to adopt more sustainable and community-oriented models. Specific background: Kampung Lali Gadget in Sidoarjo is a community-owned tourism village that applies Community Based Tourism (CBT) to promote digital detox through traditional games and environmental stewardship. Knowledge gap: Limited studies have analyzed how CBT operationalizes sustainability across economic, social, cultural, environmental, and political dimensions in a single tourism village. Aims: This study analyzes the implementation of CBT in Kampung Lali Gadget and identifies challenges in those five dimensions. Results: Using a descriptive qualitative approach, the study finds increased local income, strengthened social cohesion, cultural preservation, and improved environmental practices, but also uneven job creation, limited waste-sorting facilities, weak integration of village traditions, and resistance from some actors. Novelty: The study offers a holistic application of Suansri’s CBT framework in a gadget-free tourism village context. Implications: Findings inform policies on sustainable tourism governance and community empowerment. Highlights: CBT in Kampung Lali Gadget supports multi-dimensional sustainability. Shows benefits for locals but also highlights social, job, and waste challenges. Applies Suansri’s CBT framework in a unique gadget-free tourism setting. Keywords: Community Based Tourism, Sustainable Tourism, Kampung Lali Gadget, Digital Detox, Village Empowerment